Coactivation During Dynamometry Testing in Adolescents With Spastic Cerebral Palsy. Issue 9 (1st September 2016) - Eken, Maaike M.; Dallmeijer, Annet J.; Doorenbosch, Caroline A.M.; Dekkers, Hurnet; Becher, Jules G.; Houdijk, Han
Abstract: Background: Dynamometry has been used extensively to measure knee extensor strength in individuals with cerebral palsy (CP). However, increased coactivation can lead to underestimation of knee extensor strength and, therefore, reduce validity of strength measurements. It is yet unknown to what extent coactivation occurs during dynamometry testing and whether coactivation is influenced by severity of CP, load levels, and muscle fatigue. Objectives: The aims of this study were: (1) to investigate coactivation in adolescents with and without CP during dynamometer tests and (2) to assess the effect of Gross Motor Function Classification System (GMFCS) level, load level, and muscle fatigue on coactivation. Design: A cross-sectional observational design was used. Method: Sixteen adolescents with CP (GMFCS levels I and II: n=10/6; age range=13–19 years) and 15 adolescents without CP (n=15; age range=12–19 years) performed maximal isometric contractions (maximal voluntary torque [MVT]) and a series of submaximal dynamic contractions at low (±65% MVT), medium (±75% MVT), and high (±85% MVT) loads until fatigue. A coactivation index (CAI) was calculated for each contraction from surface electromyography recordings from the quadriceps and hamstring muscles. Results: Adolescents with CP classified in GMFCS level II showed significantly higher CAI values than adolescents classified in GMFCS level I and those without CP during maximal and submaximal contractions. No differences were observed among load levels. During the series of fatiguing submaximal contractions, CAI remained constant in both the CP group and the group with typical development (TD), except for adolescents with TD at the low-load condition, which showed a significant decrease. Limitations: Electromyography tracings were normalized to amplitudes during maximal isometric contractions, whereas previous studies suggested that these types of contractions could not be reliably determined in the CP population. Conclusion: Coactivation was higher in adolescents with CP classified in GMFCS level II than in adolescents with TD and those with CP in GMFCS level I at different load levels. Within all groups, coactivation was independent of load level and fatigue. In individuals with CP, coactivation can lead to an underestimation of agonist muscle strength, which should be taken into account while interpreting the results of both maximal and submaximal dynamometer tests.